EVALUATION OF TOMATO GERMPLASMS (SOLANUM LYCOPERSICUM L.) FOR GENETIC DIVERSITY USING MORPHO-AGRONOMIC TRAITS AND FRUIT LYCOPENE CONTENT - Adubi Amos Oladimeji; Durodola Felicia Adejoke; Azeez Musibau Adewuyi (Acta Scientifica Malaysia)
Tomato germplasm consisting of eighteen accessions and eight landraces were evaluated for morpho-agronomic traits and fruit-lycopene content to assess genetic diversity for fruit yield and quality improvement. Results obtained showed significant variability for the characters studied (p<0.05). The range of number of fruits per plant was 1.90-33.30 with the highest in L00169, while lycopene content was 2.562-13.312 μg with the highest in ABE. Positive and significant (p<0.01) correlations were recorded for number of fruits at 75 days (NOF) versus number of fruits per plant (FPP) (r = 0.916) while negative correlation was obtained for weight of fruit (WGH) versus number of fruits per plant (FPP) (-0.499). High heritability with high genetic gain was estimated for leaf area (LEA) and lycopene content (LCP). The first three principal components accounted for 63.63% of the observed variation. The 24 accession/landraces were grouped into three (Clusters I, II, and III) based on the dendrogram’s clustering structure. Cluster III had the greatest intra-cluster distance while Clusters III and I had the most inter-cluster distance. In conclusion, these results can be utilized to choose accessions that will serve as the starting point for breeding to improve tomato lycopene content and fruit yield